Sustainable heritage costumes: a review of Malay manuscript in the Malay Peninsula / Fathini Faudzi and Rohana Zur - Faudzi, Fathini; Zur, Rohana (Faculty of Art and Design, 2021)
Sustainability has existed in great civilisations across the globe for thousands of years without officially being recognized as 'sustainable'. According to the National Environment Policy Act 1969 (NEPA), 'sustainable' is defined as something that benefits current and future generations in keeping the planet's resources safe by the movement of economy. Later, in academic debates and discussions in the business area, there are more than hundreds of definitions of "sustainability" which are referring to humans, ethics, business, and many more (Marrewijik, 2003). Zooming in on the Asian continent, where the Malay Peninsula is located, the people have been applying sustainable concepts for ages in various contexts including costume making. The process of garment making is from scratch where all the natural resources are used which include motifs, philosophies and natural items such as grass, thatch, animal skin, and many more until the introduction of weaving in the Malay world. However, the use of costume proses, vocabularies, and fractured words in most Malay manuscripts is difficult and confusing to understand. Studies conducted in this area are also not as extensive. This paper provides a short overview of related research towards the suitability issue which comes from costume Malay heritage manuscripts by using textual analysis to create awareness on appreciating the old art heritage that can be promoted to open the minds of the next generation.